Drivers of emerging market cross border mergers and acquisitions: evidence from the Indian IT industry. Issue 4 (2nd October 2017) - Varma, Sumati; Kar, Rabi Narayan; Soni, Amit; Suder, Gabriele
Abstract: The present study examines the drivers of cross border mergers and acquisitions (CBMA) from the Indian information technology sector for the period 2000–2011. It uses a multi-theoretic analysis rooted in the resource-based view and network theory to examine 354 deals from 74 firms. Empirical estimation using a Poisson panel regression model found that a firm's financial resources, capability, prior international experience and parental network have a significant positive influence on CBMA activity. A unique finding of the paper is the strong presence of the Born Global engaging in CBMA as their mode of foreign market entry. This paper thus adds to the literature on internationalisation of emerging market multinational enterprises and specifically about technology-based Indian firms.